The Research Competence: Acquisition and Development Among Undergraduates in Education Sciences - Ciraso-Calí, Anna; Martínez-Fernández, J. Reinaldo; París-Mañas, Georgina; Sánchez-Martí, Angelina; García-Ravidá, Laura B. (Frontiers in Education, 2022)
Known as one of the competences of the 21st century, research competence can help students navigate through the complexities of a continuously shifting world. This study aims to analyze the acquisition and development of this competence in a sample of 154 undergraduate students of two bachelor’s degrees in Education Sciences (Social Education and Pedagogy) of the Universitat Autònoma de Barcelona (Spain). We conducted a three-phase study, in which (1) the learning outcomes related to research competences declared in the syllabi were identified and mapped through a content analysis of each syllabus; (2) students’ perceptions about the development of these learning outcomes were gathered through a questionnaire; and (3) guidelines to foster research competences among these undergraduates were explored by a Delphi panel technique. The results show that communicative skills and state-of-art reviewing skills are the least present across the courses of both degrees. The design of research competency acquisition across courses is uneven and does not seem clearly articulated. The students’ perception is consistent with the shortcomings, or disarticulation, observed in the curriculum analysis. They consider that the most poorly acquired competencies are the state-of-the-art reviewing, content knowledge, and communicative skills. Apparently, more emphasis is given to reflective thinking and communicative skills; but still, it is necessary to strengthen the acquisition of scientific content, the search for trustworthy information. These results were discussed with two panels of experts from which guidelines were defined to improve the acquisition, development, and evaluation of the research competence through university training in this field.